Geplante Erinnerung. Vom Raumwissen zum Erinnerungsort in der kooperativen Stadtplanung. - Singh, Ajit; Meißner, Kathrin (Deutsches Institut für Urbanistik, 2021)
Die Art und Weise, wie sich Gesellschaften an historisch bedeutsame Ereignisse und Epochen erinnern, ist normalerweise an Räume gebunden. Insbesondere Erinnerungsorte tragen zur Materialisierung räumlichen Wissens und zur Verräumlichung von Erinnerungskulturen bei. Der Fokus des Artikels liegt jedoch weniger auf der Nutzung, sondern auf der kommunikativen (Re-)Konstruktion von Erinnerungsorten als Ergebnis partizipativer Stadtplanung. Am Beispiel des öffentlichen Stadtplanungsprozesses des sogenannten Dragonerareals in Berlin-Kreuzberg untersuchen Ajit Sing und Kathrin Meißner, wie historisches Wissen etabliert und dieses Wissen für die zukunftsorientierte Planung eines Erinnerungs- und Lernortes gesellschaftlich bedeutungsvoll gemacht wird.

The way societies remember historically significant events and periods is usually tied to spaces. Places of remembrance in particular contribute to the materialisation of spatial knowledge and to the spatialisation of cultures of remembrance. However, this article focuses less on the use, but rather on the communicative (re)construction of places of remembrance as a result of participatory urban planning. We follow the thesis that the discursive production of a historical narrative of place is of particular importance because it objectifies spatial knowledge in a communicative and meaningful way. Using the example of the public urban planning process of the so-called Dragonerareal in Berlin-Kreuzberg, we examine how historical knowledge is established and how this knowledge is made socially meaningful for the future-oriented planning of a place of remembrance and learning. On the basis of reports and digital documentations of the planning process, we reconstruct a) how a place-specific narrative is communicatively established by the actors b) the relevance of social events for the legitimisation of the narrative c) and the significance of affective accessibility to the place of memory.
Keywords: Stadtgeschichte; Militärgelände; Historisches Gebäude; Nutzungsplanung; Geschichtsbewusstsein; Raumbezogenheit; Planungsprozess; Planungsbeteiligung; Öffentlichkeitsbeteiligung; Partizipation; Wissenstransfer; Planungskooperation; Erinnerungsort